Addition of Probiotic Dosages in Artificial Feed for Growth and Survival Rate of Green Catfish (Hemibagrus nemurus) - Saruksuk, Lucia Noralita; Alawi, Hamdan; Aryani, Netti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                             Artificial feed is one of the alternative diet to replace natural foodfor fish larvae.  The addition of probiotics to paste feed could  improve the digestibility of larvae. Probiotics are cultured products or live microbial feed suplements, which beneficially affect the host by improving the intestinal microbial balance. The aim of the research was to evaluate the addition of probiotic dosages to artificial feed on growth and survival rate of green catfish larvae. This research was conducted from July until September 2018 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Faculty Riau University. The treatments in this research wereP0 (0 ml/kg feed), P1 (2 ml/kg feed), P2 (4 ml/kg feed), P3 (6ml/kg feed). The 8 days old larvae were rearing in 15 litreaquarium at stocking density 2 larvae/l for 40 days. Feeding was given 3 times/day at the rate 30% of biomass. Result showed  that the larvae fed 4 ml probiotic / kg  feed was the highest growth (1,7 g, 5,18 cm and 12,8 %/day), the best feed efficiency was 40,2% and the highest survival rate was 70%.Keywords :Green Catfish Larvae; Paste Feed; Probiotic; Growth;Survival Rate